Handbook on biodegradation and biological treatment of hazardous organic compounds - Agteren, Martin H. van (Kluwer Academic Publishers, 1998)
The introduction of synthetic organic chemicals into the environment during the last few decades has given rise to major concern about the ecotoxicological effects and ultimate fate of these compounds. The pollutants that are considered to be most hazardous because of their intrinsic toxicity, high exposure level, or recalcitrant behavior in the environment have been placed on blacklists and other policy priority lists. The fate of synthetic compounds that enter the environment is mainly determined by their rate of biodegradation, which therefore also has a major effect on the degree of bioaccumulation and the risk of ecotoxicological effects.